PERSEPSI DAN KESIAPAN GURU SEKOLAH DASAR DALAM MENGIMPLEMENTASIKAN COMPUTATIONAL THINKING PADA KURIKULUM MERDEKA: STUDI MIXED METHODS DI KABUPATEN [X] - Lukman Junaedi; Achmad Zakki Falani; Natalia Damastuti; Latipah Latipah; Muchamad Arif (Universitas Narotama, 2026)
This study aims to analyze the level of perception and readiness of Elementary School (SD) teachers in implementing Computational Thinking (CT) within the Merdeka Curriculum. Although CT has been integrated into the national curriculum, empirical data on the specific readiness of SD teachers in the Merdeka Curriculum era remains very limited. This study employed a mixed methods approach with a sequential explanatory design. Quantitative data were collected through a survey of 120 SD teachers using the CT-Teacher Readiness Scale (40 items, ? = 0.91) developed and validated in this study, followed by in-depth interviews with 12 purposively selected teachers. Results indicated that most teachers (65.8%) were in the unprepared to underprepared category for CT implementation, with an overall mean score of 54.3% (SD = 10.9). Technology readiness (M = 44.1%) was the lowest dimension, while motivation and attitude (M = 68.9%) was the highest. Spearman correlation analysis revealed that CT training (r = 0.512, p < 0.001) and technology access (r = 0.443, p < 0.001) were significant predictors of teacher readiness, while years of service correlated negatively (r = -0.387, p < 0.001). Qualitative findings revealed three main themes: (1) unclear guidelines for CT implementation in Merdeka Curriculum teaching modules, (2) limited availability and quality of CT training, and (3) significant digital divide between young and senior teachers. This study contributes a validated CT-Teacher Readiness Scale instrument and an evidence-based teacher readiness profile that can serve as a policy foundation for CT teacher training at the SD level. Keywords: Computational Thinking, Teacher Readiness, Merdeka Curriculum, Elementary School, Mixed Methods, CT-Teacher Readiness Scale